Implementation of Green Business Strategy in Increasing Competitiveness of Manufacturing Companies - Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Soni, Muhamad; Nabila, Syifa Thahira (Entrepreneurship Faculty, Universitas Garut, 2024)
Business management is becoming crucial for manufacturing companies looking to increase their competitiveness in a market that is increasingly focused on sustainability. Climate change and the negative impact of industrial activities on the environment have pushed companies to adopt more sustainable business practices. The purpose of this study is to analyze environmentally friendly businesses in improving competency in the manufacturing sector. This research method uses qualitative descriptive itself providing a framework that allows researchers to understand and describe the social context and behavior of individuals or groups, data collection techniques with observation, and analysis of documentation studies, data analysis techniques using data reduction, data presentation and data verification through Nvivo 12 software. The results of the data analysis identified that consistency in implementing green marketing practices contributed greatly to positive results in marketing. The implementation of green business strategies in the manufacturing industry not only contributes to environmental sustainability. Therefore, implementing environmentally friendly business management encourages the creation of good competence in the business sector.